2017
DOI: 10.1590/1806-9282.63.07.636
|View full text |Cite
|
Sign up to set email alerts
|

Use of SGLT-2 inhibitors in the treatment of type 2 diabetes mellitus

Abstract: Summary Introduction: Diabetes mellitus is one of the most common chronic diseases in the world, with high morbidity and mortality rates, resulting in a greatly negative socioeconomic impact. Although there are several classes of oral antidiabetic agents, most of the patients are outside the therapeutic goal range. Objective: To review the use of SGLT-2 inhibitors in the treatment of type 2 diabetes mellitus, focusing on their favorable and unfavorable effects, as well as on cardiovascular profile. Method: A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Therefore, agents that control hyperglycemia safely while also preventing or treating DKD are urgently needed. Over the past three decades, discovery and elucidation of the role of sodium symporters in glucose reabsorption, and thereby glucose homeostasis, have pointed to sodium-glucose cotransporter 2 (SGLT2) inhibition as a viable therapeutic target (16)(17)(18)(19). In cardiovascular disease (CVD) outcomes trials conducted for safety, SGLT2 inhibitors actually have demonstrated clear benefits on CVD and CKD.…”
mentioning
confidence: 99%
“…Therefore, agents that control hyperglycemia safely while also preventing or treating DKD are urgently needed. Over the past three decades, discovery and elucidation of the role of sodium symporters in glucose reabsorption, and thereby glucose homeostasis, have pointed to sodium-glucose cotransporter 2 (SGLT2) inhibition as a viable therapeutic target (16)(17)(18)(19). In cardiovascular disease (CVD) outcomes trials conducted for safety, SGLT2 inhibitors actually have demonstrated clear benefits on CVD and CKD.…”
mentioning
confidence: 99%
“…While SGLT1 is the main glucose transporter in the small intestine, SGLT2 is predominantly expressed on epithelial cells surface on the lining of the S1 segment of the proximal convoluted tubule (Fioretto & Avogaro, 2017). Studies have shown DN to be the most selective for SGLT2 (1200-fold over SGLT1), which could be the better drug for the treatment of type 2 diabetes (Santos et al, 2017;Wilding et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2 inhibitors such as DN and dipeptidyl peptidase-4 (DPP-4) inhibitors like SN is potentially beneficial in achieving glycemic control without the risk of hypoglycemia or weight gain treatment of type 2 diabetes (Santos et al, 2017). A recent study suggests that in patients with type 2 diabetes, combination therapy (Ji et al, 2016) provided additional clinical benefit and is well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is one of the most common types of chronic disease with extensive morbidity and mortality worldwide (1). Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and is a frequent cause of preventable blindness worldwide (2).…”
Section: Introductionmentioning
confidence: 99%